Democracy Is Democracy Is Democracy? Changes in Evaluations of International Institutions in Academic Textbooks, 1970–20101. Issue 2 (28th April 2014) - Dingwerth, Klaus; Lehmann, Ina; Reichel, Ellen; Weise, Tobias
Abstract : This article examines what democracy means when it is used in academic textbook evaluations of international institutions and how the meaning of the term "democracy" in such evaluations has changed over time. An analysis of 71 textbooks on international institutions in the policy areas of international security, environmental, and human rights politics leads us to several answers. We observe slight changes in relation to three aspects. First, the range of democracy‐relevant actors expands over time, most notably in relation to nonstate actors as important participants in (or even subjects of) international policymaking. Second, representational concerns become more relevant in justifying demands for greater participation in international institutions. Third, international organizations are increasingly discussed not only as subjects that enhance the transparency and accountability of the policies of their member states, but also as the objects of democratic demands for transparency and accountability themselves.